Nobility vs. obscenity in Brazilian translations of Hamlet: a consideration of possible relationships between the translators and the author - Vollet, Neuza Lopes Ribeiro (TradTerm, 1998)
The main point discussed in this text is the translator’s relationship with the original author from a post-modern perspective, according to which the author’s meaning of words, his conditions of work writing, his desires and motivations and dramatic objectives can not be recovered. They can only be interpreted from a specific historical, cultural and ideological perspective. I will examine two distinct approaches related to sexual language in Hamlet, by William Shakespeare, in Brazilian translations, to argue that the differences in handling such issue depend on the translators adopting different concepts about the author.